DAMPAK GLOBALISASI EKONOMI TERHADAP PERDAGANGAN INTERNASIONAL DI PASCA PANDEMI (2020-2024) - Tutiana Bayati; Tiara Ajeng Dewita, Sri Rahmanita, Raissa Puan Andrina, Bagus Hermansyah; Dwita Sakuntala (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the impact of economic globalization on international trade during the COVID-19 pandemic period (2020-2024). Using a qualitative method based on literature and previous empirical studies, the research examines changes in international trade patterns, the challenges faced by countries, and the adaptive strategies implemented to address global challenges. The data used in this study were sourced from scholarly articles published between 2020 and 2024. The findings indicate that economic globalization has persisted despite various challenges arising from the pandemic, with technology and trade policies serving as key determinants. This study highlights the importance of flexible trade policy adaptations to enable countries to remain competitive in the global market